SOME ISSUES REGARDING ARTIFACTS - Paula TOMI (Studia Universitatis Babeș-Bolyai. Philosophia)
When it comes to artifacts, the functional accounts define them as objects that have an intended function. This function is considered essential for them and is used to classify artifacts and differentiate them. However, functional accounts of artifacts face some serious criticism. It seems that a function is neither essential, nor sufficient for an artifact. Thomasson offers a new perspective on artifacts. The author defines artifacts based on their intended feature. A feature may, of course, be a function but does not have to be just that. Generally speaking, intended features are norms of how to treat that specific artifact. Such an account is able to escape the criticism raised against functional accounts. In this article is presented Baker’s functional account of artifacts and some criticism that can be raised for such an account. The second part of the article critically introduces Thomasson’s account for artifacts. The aim of this article is to support Thomasson’s account against a functional perspective.